2009
DOI: 10.3347/kjp.2009.47.3.303
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Intestinal Protozoan Infections among Gastroenteritis Patients during a 3-Year Period (2004-2006) in Gyeonggi-do (Province), South Korea

Abstract: The incidence and etiology of parasite-associated gastroenteritis during 2004-2006 in Gyeonggi-do (province), South Korea was determined by means of antigen detection ELISA on 6,071 stool specimens collected from 6 general hospitals. At least 1 parasitic agent was detected in 3.4% (208/6,071) of the stool samples. Among these, Giardia lamblia was the most numerous (152 cases; 2.5%), followed by Entamoeba histolytica (25 cases; 0.4%), Cryptosporidium parvum (23 cases; 0.4%), and mixed infections (8 cases; 0.1%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
(10 reference statements)
0
13
0
1
Order By: Relevance
“…However, enteric parasites-mainly protozoa-are isolated from 1% to 65% of patients with diarrhea in various settings. The relative prevalences of enteric protozoa reported in several developed countries in outbreak and nonoutbreak settings among humans are reported in Table 1 (1, 11,12,24,60,85,90,96,128,144,184,192,193,204,215,225,247,248,255,264,265,301,335,355,370,395,416,417,425,442,444,452,467). Giardia intestinalis (0.2% to 29.2% of cases), Cryptosporidium spp.…”
Section: Distribution In Developed Countriesmentioning
confidence: 99%
“…However, enteric parasites-mainly protozoa-are isolated from 1% to 65% of patients with diarrhea in various settings. The relative prevalences of enteric protozoa reported in several developed countries in outbreak and nonoutbreak settings among humans are reported in Table 1 (1, 11,12,24,60,85,90,96,128,144,184,192,193,204,215,225,247,248,255,264,265,301,335,355,370,395,416,417,425,442,444,452,467). Giardia intestinalis (0.2% to 29.2% of cases), Cryptosporidium spp.…”
Section: Distribution In Developed Countriesmentioning
confidence: 99%
“…Cryptosporidium parvum are the major parasitic organisms causing childhood diarrhea in developing countries [16][17][18]. Although these parasites do not usually cause life-threatening disease, they are still important infectious agents, especially in infants.…”
Section: Giardia Lamblia Entamoeba Histolytica Andmentioning
confidence: 99%
“…In recent years, numerous bacterial, viral, and parasitic agents are considered the main cause of gastroenteritis. Viral agents are the cause of the high rates of gastroenteritis, followed by bacterial and parasitic agents (1,5). The human rotavirus is the most common etiologic agent of pediatric infections, which annually causes 125 million cases of diarrhea and more than 600 000 childhood deaths worldwide (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Protozoan diarrhea is also distributed around the globe. Giardia lamblia, Entamoeba histolytica, and Cryptosporidium parvum are the mostly reported protozoan pathogens that cause gastroenteritis (4,5). Studies showed that approximately 100,000 deaths followed by gastroenteritis are related to protozoan species (12).…”
Section: Introductionmentioning
confidence: 99%